To introduce and measure the effectiveness of case based learning in physiology - Bansal, Monika; Goyal, Manoj (International Journal of Research in Medical Sciences, 2017)
Background: Student/learner centered strategies are needed to promote active learning in the students. Medical Council of India (MCI) also encourages learner centric approaches. Objectives of the study were to develop case scenarios for teaching in Physiology and use them to teach 1st professional MBBS students and to evaluate the impact of this intervention on students’ learning. Methods: After the approval from Institutional Ethics Committee (IEC) the study was conducted on MBBS 1st professional students. The students were taught two topics using CBL strategy. Pre-post test score were taken for evaluation of students’ learning. Students’ feedback was taken to elicit their perceptions about the effectiveness of the strategy. Faculty feedback was also taken for feasibility and implementation of CBL. Results: Majority of the students were satisfied with the session. Majority felt it to be a good learning experience and many wanted to attend more such sessions. Difference in the pre-post test scores was statistically highly significant. Conclusions: CBL proved to be an interesting and effective active learning strategy. More of such sessions should be conducted to engage the students as felt by students and faculty both.